Dukungan Program Kebersihan Kelurahan Melalui Pemasangan Plang Himbauan Oleh Mahasiswa KKN Universitas Dehasen Bengkulu - Oktariani, Sri; Jahda, Amila Tarina; Anjjely, Sellina Dwi; Anisa, Rici; Alpino, Shendi Putra; Muhammad; Yanto, Yanto; Fitriano, Yun; Susanti, Neri (Jurnal Karya Nyata Pengabdian, 2025)
The involvement of community service (KKN) students from Universitas Dehasen (UNIVED) in supporting the local government's policy in Pematang Gubernur Sub-district regarding environmental cleanliness programs through the installation of cleanliness signage. The research employed a qualitative descriptive approach, with data collected through in-depth interviews, direct observation, and documentation. Informants included KKN students, local government officials, and community members. The findings reveal that student involvement extended beyond technical tasks such as signage installation to include planning, community education, and persuasive dissemination of cleanliness messages. The installation of signage proved to have a positive impact by increasing public awareness to avoid littering and fostering collective behavior in maintaining a clean environment. Supporting factors for the program's success included active community participation, strategic placement of the signage, and the humanistic communication approach used by the students. This study concludes that collaboration between students, local government, and the community can create constructive social change in community-based environmental management. Similar programs are recommended for continued development with sustained support from multiple stake holders.